The development of ‘ilm tafsir in Malaysian education system - Fatah Yasin, Raudlotul Firdaus (2018)
The development of science of tafsir in Malaysia is quite advanced but was not formally established as a discipline of science. The discussion is more towards the science of tafsir itself rather than studying the problems in society and its solutions from the perspective of Qur’an. Employing qualitative method, this paper aims at studying the experience of Malaysia in the development of science of tafsir, the historical overview and its impact towards educational system. The presentation also seeks to identify the challenges and obstacles that might have hindered the progress of developing a more integrated methodology of science of tafsir that may offer practical solutions to address the current religious, socio-political and economic problems facing the Muslim society from the Qur’anic perspectives